2012
DOI: 10.1128/aac.01537-10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ceftobiprole Activity against a Variety of Gram-Negative Pathogens, Including Escherichia coli, Haemophilus influenzae (β-Lactamase Positive and β-Lactamase Negative), and Klebsiella pneumoniae, in a Rabbit Meningitis Model

Abstract: Ceftobiprole medocaril, a new cephalosporin, is highly active against a broad spectrum of Gram-positive and Gram-negative clinical pathogens, including methicillin-resistant Staphylococcus aureus (MRSA) and penicillin-resistant pneumococci. In this study, we tested ceftobiprole against various Gram-negative pathogens in a rabbit meningitis model and determined its penetration into the cerebrospinal fluid (CSF). In this animal model, ceftobiprole produced an antibacterial activity similar to that of cefepime ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The newer lipoglycopeptides have low CNS penetration: for telavancin CNS 0.1% in non-inflamed meninges and 2% in inflamed meninges [46] and for oritavancin 2%e5% in rabbit models of meningitis [47]. The newer cephalosporins with an anti-methicillinresistant S. aureus spectrum of coverage might hold promise as their CNS penetration is similar to that of other cephalosporins: for ceftaroline 3% in non-inflamed meninges and 14%e15% in inflamed meninges [48,49], and for ceftobiprole 2% and 16%, respectively [50], both in rabbit models. Clinical data are unavailable to date.…”
Section: Gram-positive Bacteriamentioning
confidence: 99%
“…The newer lipoglycopeptides have low CNS penetration: for telavancin CNS 0.1% in non-inflamed meninges and 2% in inflamed meninges [46] and for oritavancin 2%e5% in rabbit models of meningitis [47]. The newer cephalosporins with an anti-methicillinresistant S. aureus spectrum of coverage might hold promise as their CNS penetration is similar to that of other cephalosporins: for ceftaroline 3% in non-inflamed meninges and 14%e15% in inflamed meninges [48,49], and for ceftobiprole 2% and 16%, respectively [50], both in rabbit models. Clinical data are unavailable to date.…”
Section: Gram-positive Bacteriamentioning
confidence: 99%
“…Ceftobiprole demonstrates in vitro activity against S. aureus resistant to linezolid, vancomycin, and daptomycin [15], and ceftriaxoneresistant S. pneumoniae [16,17]. It also demonstrates superior bactericidal activity to daptomycin, linezolid, and vancomycin in several animal models of endocarditis [18,19], osteomyelitis [20,21], meningitis [22], mediastinitis [23], and peritonitis [24], and good efficacy in animal models of pneumonia and skin infections [25,26]. Ceftobiprole is therefore a promising agent with potential utility for difficult-to-treat infections.…”
mentioning
confidence: 99%
“…In addition, little is known regarding the penetration of cerebrospinal fluid (CSF) for ceftobiprole. Stucki et al [ 65 ] found that ceftobiprole penetration was approximately 16% in inflamed meninges, compared to approximately 2% in uninflamed meninges in a model for rabbit meningitis. In primary meningitis caused by S. pneumoniae (including strains resistant to penicillin and ceftriaxone) and the secondary post-operatory meningitis that requires both Gram-positive and Gram-negative coverage, ceftobiprole may be a beneficial option.…”
Section: Discussionmentioning
confidence: 99%